Graphene enhanced paraffin nanocomposite based hybrid cooling system for thermal management of electronics. (25th December 2019) - Joseph, Mathew; Sajith, V.
Graphical abstract: Highlights: Study of Hybrid cooling system for electronics under pulsed/uniform thermal loads. Study of thermal properties of paraffin/graphene composites. Enhancement in thermal conductivity up to 60% for 0.5 wt% of graphene in paraffin. Reduction in fan operation time with paraffin/graphene inclusion. Energy savings for paraffin/graphene heat sink up to 23%. Abstract: Hybrid cooling systems combining forced convection with passive phase change material (PCM) based heat sink is an ideal solution for long-term cooling of high power electronics. The effectiveness of composite PCM with graphene nanofillers on transient performance of a hybrid thermal control system was investigated experimentally under uniform and periodic pulsed heat loads. Graphene was synthesized by liquid-phase exfoliation and paraffin/graphene composite was prepared for various concentrations. The thermo-physical properties of paraffin/graphene composite were measured. Transient thermal responses of heat sink with paraffin/graphene composite (HS-Gr/PCM) and paraffin (HS-PCM) were compared to heat sink without paraffin (HS) for passive and hybrid cooling mode configurations. The thermal performance of HS-Gr/PCM was far superior to HS and HS-PCM in all thermal loading scenarios. In passive mode, maximum of 6 °C lower steady-state temperature was attained for HS-Gr/PCM relative to HS under uniform thermal load. In hybrid mode, time to reach fan onset temperature was enhanced by 109%, 122% and 110% for HS-Gr/PCM over HS, corresponding to periodic heat pulses with duty factors 0.5, 0.79 and 0.9 respectively. Experiments with hybrid cooling system showed 11–23% enhancement in fan energy savings for HS-Gr/PCM as compared to HS at different periodic heat pulses.